Proposing a model for foreign market selection in the ground engineering slurries industry: the special case of Ground Tech - Correia, Jorge Filipe de Jesus Sousa (2011)
SMEs that develop their business in niche markets need to look to opportunities in other markets (foreign countries) in order to be able to sustain overtime the business growth. This work proposes a model for foreign market selection in the industry of Ground Engineering soil stabilisation slurries. This study based on the Hollensen’s international market selection model, the author proposes an adapted and expanded model for foreign market selection. Above all, the aim of this work is to propose a practical implementation of the model in order to support decision making for foreign market selection.